Technical Efficiency of Yam Producers: The Case of the Municipality of Glazoué in Benin - ADANGUIDI, JEAN; AMEGNAGLO, Cocou Jaurès (My University, 2020)
In Benin republic, yam plays an important role both in production systems and in people’s food security and trade. In view of the decline in agricultural yields in recent years combined with strong population growth, it is essential today to analyse the technical efficiency of yam producers in order to formulate the best recommendations for relaunching yam production. The objective of this paper is to analyse the technical efficiency of yam producers in Benin and its determinants. To achieve this objective, data were collected from 150 yam producers living in the Municipality of Glazoué. A stochastic production frontier is used to analyse the technical efficiency of the yam producer. The results revealed that the mean efficiency score of producers is around 80%. This implies that yam production could be increase by 20% through better use of available resources such as land, labour, herbicides, taking into account the state of technology. Access to credit and mobile phone ownership increase the inefficiency of actors while experience in agricultural production, age and household size reduce the inefficiency of producers.
Keywords: Benin; determinants; stochastic frontier production function; technical efficiency; yam